Efeito do uso de contraceptivos orais e do treinamento pliométrico na biomecânica do membro inferior em atividades funcionais - Lobato, Daniel Ferreira Moreira (2012)
The aim of Study 1 was to evaluate the effects of using oral contraceptives (OC) on the hip and knee kinematics of healthy women during single-leg squat. Forty two volunteers were divided into two groups: women who had used OC (n= 21) and women who did not use OC (n= 21). The knee abduction/adduction, hip abduction/adduction and medial/lateral rotation excursions (maximum and at 75º of knee flexion) were calculated for the dominant limb during single-leg squat. No significant difference was verified between the groups regarding the maximum excursion of knee abduction (p= 0.26) or hip adduction (p= 0.10) and medial rotation (p= 0.94). When considering the knee flexion at 75º, no significant difference was verified between the groups regarding the excursion of knee abduction (p= 0.31) or hip adduction (p= 0.11) and medial rotation (p= 0.85). These results suggest that the use of OC does not influence the hip and knee kinematics during single-leg squat. As a complement, the aim of Study 2 was to evaluate the effects of using OC on the hip and knee kinematics of healthy women during anterior stair descent. Forty volunteers were divided into two groups: women who had used OC (n= 20) and 2 - women who did not use OC (n= 20). The knee abduction/adduction, hip abduction/adduction and medial/lateral rotation excursions were calculated for the dominant (supporting) limb during anterior stair descent. No significant difference was verified between the groups regarding the maximum excursion of knee abduction (p= 0.58) or hip adduction (p= 0.29) and medial rotation (p= 0.42). When considering the knee flexion at 50º, no significant difference was verified between the groups regarding the excursion of knee abduction (p= 0.92) or hip adduction (p= 0.50) and medial/lateral rotation (p= 0.19). These results suggest that the use of OC does not influence the hip and knee kinematics during anterior stair descent. The aim of Study 3 was to verify the effects of eight-week plyometric training (PT) on hip and knee kinematics and on eccentric hip and knee torques, as well as on lower limb functional performance in healthy women. Thirty-six females were divided into a training group (TG; n= 18), and a control group (CG; n= 18). Kinematic analyses of the hip and knee was carried out during the single-leg squat and the functional performance was evaluated by way of the triple hop (TH) test and the six-meter timed hop (STH) test. The eccentric hip abductor, adductor, lateral rotator and medial rotator as well as the knee flexor and extensor torques/body weight were measured using an isokinetic dynamometer. After 8 weeks, the TG showed a decrease in maximum excursion to knee abduction (p= 0.009) and in maximum excursion to hip adduction (p<0.001), as well as in the excursion to hip adduction at 75º of knee flexion (p=0.002). Moreover, the TG significantly increased the values obtained in the TH test (p=0.05) and significantly decreased those obtained in the STH test (p<0.001) after intervention. However, there was no significant change on hip and knee eccentric torques. Thus, eight weeks of PT were effective to improve hip and knee kinematics and functional performance of women in hop tests. However this was apparently not an effective method to promote strengthening of the hip and knee muscles when used alone